PENGEMBANGAN BAHAN AJAR MENULIS KARYA ILMIAH DALAM PENGAJARAN BAHASA INDONESIA DI STIKOM KOTA JAMBI - Sarmadan Sarmadan (Jurnal Ilmiah Universitas Batanghari Jambi, 2017)
In teacing and learning process in a class room the using of learning mareial is very important. Leaning material is one of learning sources in teaching and learning activity. Teaching material that serve in it is also take part in that optimalization learning process. Theres no specific learning sources yet, especialy that related to the writing of research paper make a specific problem in lecture process at Sekolah Tinggi Ilmu Komputer Kota Jambi.Related to that problem, is needed a specific learning material in writing of researc paper that deal with students need and characteristic to in crease learning result the development method that used is research and development (R&D).  This method is developed by Borg & Gall (1989), Then, R&D method is modified by Sukmadinata (2009) into three steps, that is (1) preface study, (2) method development, and (3) method experiment. Learning material development is deciden to make a participation tim, involve: education technology expert designer lerning expert, subjek material expert, and student.Result of education technology expert is 75% for learning material, it in good level if compatibled tabel. Then designer learning for learning material got 80,09%, it is in a very good level in table. Result of subjek material learning expert is 80,76%, it in good level if compatibled with table. Result of small group toward learning material process, 75%, it in good level if caompatible with table. During the experiment process, the revision done continuely to get learning produk that deal with the users need.Keywords: learning material development, the writing of the research papaer